The emotional intelligence’s effect on job satisfaction of bank salespeople - Meutia Karunia Dewi; Achmad Sudjadi; Wiwiek Rabiatul Adawiyah (Universitas Hayam Wuruk Perbanas, 2014)
This research tested the effect of emotional intelligence (EI) on job satisfaction (JS), with positive affect (PA) and negative affect (NA) as mediators and organizational learning capability (OLC) as a moderator. Respondents of this research are 132 salespeople of banks in Banyumas Regency, Central Java Indonesia. They completed 59 items on distributed questionnaires. Results using structural equation modeling indicated that positive effect of EI on JS was not significant; instead, the effect was significantly mediated by PA. Furthermore, EI had significant positive effect on PA and PA had significant positive effect on JS as well. Those results confirm expectation derived from Affective Events Theory regarding the role of work affectivity as an interface between personality and work attitudes. Meanwhile, EI had insignificant negative effect on NA and NA also had insignificant negative effect on JS, therefore, NA was not a significant mediator of EI’s effect on JS. Different from expectations, OLC was not a significant moderator of the effect itself.